Polymorphisms in the organic anion transporting polypeptide genes influence liver parenchymal enhancement in gadoxetic acid-enhanced MRI. (October 2013) - Okubo, Hironao; Ando, Hitoshi; Kokubu, Shigehiro; Miyazaki, Akihisa; Watanabe, Sumio; Fujimura, Akio
Aim: This study aimed to investigate whether genetic polymorphisms of the organic anion transporting polypeptides influence hepatic enhancement in gadoxetic acid-enhanced MRI.Patients & methods: We analyzed the genotypes of SLCO1B1 388A>G, SLCO1B1 521T>C, SLCO1B3 334T>G and NR1H4 -1G>T and calculated the mean quantitative liver–spleen contrast ratio, as an index of liver parenchymal enhancement, in 226 patients with liver disease.Results: Multiple linear regression analysis using the mean quantitative liver–spleen contrast ratio as the dependent variable revealed that not only Child–Pugh score, but also SLCO1B1*1b haplotype (β = 0.12; p = 0.04), were significant predictors of liver parenchymal enhancement. In addition, SLCO1B3 334T>G (β = -0.18; p = 0.03) was a significant predictor when the data were analyzed in a subgroup of 117 patients, excluding the carriers of NR1H4 -1G>T, who reportedly exhibit reduced transcriptional activity of SLCO1B3 .Conclusion: These genetic variants, as well as hepatic function, may contribute to individual differences in hepatic enhancement with gadoxetic acid. Original submitted 4 March 2013; Revision submitted 10 July 2013